2006
DOI: 10.1111/j.1467-8535.2006.00641.x
|View full text |Cite
|
Sign up to set email alerts
|

Online learner’s ‘flow’ experience: an empirical study

Abstract: This study is concerned with online learners' 'flow' experiences. On the basis of Csikszentmihalyi's theory of flow, flow was conceptualised as a complex, multimentional, reflective construct composing of 'enjoyment', 'telepresence', 'focused attention', 'engagement' and 'time distortion' on the part of learners. A flow model was put forward with regard to virtual class environment in a traditional university context, comprised with flow antecedents, flow and flow consequences. Based on the model, a virtual-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
129
1
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(161 citation statements)
references
References 14 publications
9
129
1
5
Order By: Relevance
“…As this self-motivated learning is considered the best way to learn (Ghani & Deshpande, 1994), a main challenge in education is to foster learners' flow state. In this regard, research in web-based learning environments has shown that there is a positive correlation between the flow state that students might reach when using these environments and their learning outcomes (Liao, 2006;Shin, 2006;Webster, Trevino, & Ryan, 1993). Positive results have also been highlighted by studies that analyzed the performance of students within multi-user virtual environments and gamebased learning environments (Faiola, Newlon, Pfaff, & Smyslova, 2013;Papastergiou, 2009).…”
Section: Introductionmentioning
confidence: 79%
“…As this self-motivated learning is considered the best way to learn (Ghani & Deshpande, 1994), a main challenge in education is to foster learners' flow state. In this regard, research in web-based learning environments has shown that there is a positive correlation between the flow state that students might reach when using these environments and their learning outcomes (Liao, 2006;Shin, 2006;Webster, Trevino, & Ryan, 1993). Positive results have also been highlighted by studies that analyzed the performance of students within multi-user virtual environments and gamebased learning environments (Faiola, Newlon, Pfaff, & Smyslova, 2013;Papastergiou, 2009).…”
Section: Introductionmentioning
confidence: 79%
“…In these empirical studies, the participants often get confused when requested to classify the standard of the skills they possess or the level of the task challenges they choose (Chen et al, 1999;Shin, 2006). The more vaguely the applied activity (related to the use of computers and the web sources) is formulated, the greater the participants' confusion is, which is probably the reason most of the current research projects in the field refer to the specialized, that is, nonuniversal tasks performed in cyberspace.…”
Section: Characteristics Of Flow As Used In Empirical Researchmentioning
confidence: 99%
“…The currently available experience leads to useful recommendations aimed at avoiding some possibly restrictive decisions as well as lessening the negative influences on the visitors and customers of the existing e-shops and at perfecting the design and the usability of the would-be e-marketing sites (Pace, 2004;Rettie, 2001;Siekpe, 2005). The educational applications of the optimal experience methodology have always been thoroughly investigated, and the cyberspace field is not an exception (Chan & Ahem, 1999;Konradt & Sulz, 2001;Konradt et al, 2003;Pearce et al, 2005;Shin, 2006). A flow experience is a significant predictor of the learners' satisfaction with the teaching courses (Shin, 2006).…”
Section: Flow In Diverse Cyberspace-related Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion of taste has been used by Per Anderhag, Per-Olof Wickman and Karim Hamza (2015) to understand how teachers help students learn to like science and it is likely that the more authentic inquiry experience for the Off-Campus in its totality led to developing their taste for science. Furthermore, Karen Beard and Wayne Hoy (2010) found that a positive academic attitude (as opposed to a general disposition) contributes for teachers to experience flow in their own learning processes, and Namin Shin (2006) reports that students' self-perception of their skills in relation to a particular challenge is important for flow. This raises questions of how the experiences of teachers and students are interrelated in inquiry teaching, and in particular what the students (and teachers) actually learned about scientific inquiry itself, for example as assessed in the work of Judith Lederman et al (2014).…”
mentioning
confidence: 99%